Switzerland : 2011 Article IV Consultation; Staff Report; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for the Switzerland. (IMF Staff Country Reports; Country Report ;, 2011)
Although progress has been made in strengthening the Swiss economy, systemic risks posed by large banks as well as revisions to the macroprudential framework are still in train. The authorities welcomed the too-big-to-fail (TBTF) legislation and intervention of the Swiss National Bank (SNB) on strengthening financial sector stability, and stressed the need of a strong macroprudential framework and a legal framework with regard to crisis prevention. The authorities supported adherence to the Swiss debt brake rule, and emphasized that sustainability of public finances should be further improved.